2008
DOI: 10.1097/mnm.0b013e328302cd10
|View full text |Cite
|
Sign up to set email alerts
|

Fluordeoxyglucose-PET study in first-episode schizophrenic patients during the hallucinatory state, after remission and during linguistic–auditory activation

Abstract: Our findings show a different pattern of regional cerebral glucose metabolism between AVH and physiological auditory activation. This feature does not support the hypothesis that AVH in acute schizophrenic patients reflects an abnormal activation of auditory-linguistic pathways. However, it does suggest that cortical regions implicated in the generation of inner speech could be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…44 However, we failed to observe a differential involvement of this area in AVHs compared with its engagement in psychotic symptoms other than AVHs. Preferential differences between the acute hallucinatory state and an antipsychotic-induced remission in frontal metabolism, as previously reported by our group, 17 could partly represent a medication effect, since some frontal regions (including the Broca area) are known to be susceptible to metabolic changes following anti psychotic treatment. [45][46][47] However, this interpretation remains to be tested in future studies directly comparing patients with schizophrenia with and without AVHs before and after treatment.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…44 However, we failed to observe a differential involvement of this area in AVHs compared with its engagement in psychotic symptoms other than AVHs. Preferential differences between the acute hallucinatory state and an antipsychotic-induced remission in frontal metabolism, as previously reported by our group, 17 could partly represent a medication effect, since some frontal regions (including the Broca area) are known to be susceptible to metabolic changes following anti psychotic treatment. [45][46][47] However, this interpretation remains to be tested in future studies directly comparing patients with schizophrenia with and without AVHs before and after treatment.…”
Section: Discussionsupporting
confidence: 78%
“…18 The patients with AVHs were part of a withingroup study reported elsewhere. 17 We also included a group of age-and sex-matched healthy controls. All participants were screened with medical history, physical examination, structural T 1 -and T 2 -weighted magnetic resonance imaging (MRI) and laboratory testing.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18 F]FDG PET has also been used to investigate the effects of antipsychotic drugs [220][221][222][223], cannabis use [224,225] and auditory verbal hallucinations [226,227] on the pattern of cerebral glucose metabolism in schizophrenia and to differentiate it from the pattern in bipolar disorder [228]. A hypothesis for pathogenesis of schizophrenia based on impaired neuronal glucose uptake by GLUT1…”
Section: Schizophreniamentioning
confidence: 99%